2020
DOI: 10.1108/ijsms-10-2019-0112
|View full text |Cite
|
Sign up to set email alerts
|

How deep is your love? Brand love analysis applied to football teams

Abstract: PurposeThe central objective is to determine the main components of a brand that become a “beloved” brand in the minds of consumers applied to football teams.Design/methodology/approachThe authors conducted a quantitative causal study using partial least squares (PLS) with a sample of 824 participants using an online questionnaire.FindingsBrand love is a construct composed of five dimensions: passion, connection with the brand, intrinsic rewards, emotional attachment and thinking and frequent use. It also demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 89 publications
0
12
0
4
Order By: Relevance
“…, 2004). When customer develops love for the brand, desire to own the brand exceeds; they feel separation distress, resistance to negative information as outcome, loyalty, willingness to invest and WOM communication (Hung and Lu, 2018; Velicia Martín et al. , 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…, 2004). When customer develops love for the brand, desire to own the brand exceeds; they feel separation distress, resistance to negative information as outcome, loyalty, willingness to invest and WOM communication (Hung and Lu, 2018; Velicia Martín et al. , 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The current research fills this gap by considering additional advantages and benefits of brand love for branding decision makers. A few research studies indicated that if customers fell in love with a brand, they showed unique emotions such as willingness to resist negative information (Bagozzi et al, 2017;Bowden, 2009), occasionally accepting potential wrongdoings from the brand (Leventhal et al, 2014), willingness to invest, positive WOM for their loved brand (Hung and Lu, 2018;Velicia Mart ın et al, 2020), brand advocacy, brand tolerance, forgiveness of brand failure (Fournier, 1998;Sarkar, 2014;Hegner et al, 2017) and willingness to pay price premium (Albert and Merunka, 2013). Thus, conceptual clarity is needed to advance the knowledge of brand trust and brand love (Drennan et al, 2015;Loureiro et al, 2017) in order to comprehend the quality of customer-brand relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…If consumers are satisfied with the brand experience, they will gradually become attached to the brand. After they become attached, they will have a deeper emotional connection with the brand based on brand love ( Velicia Martín et al, 2020 ; Gilal et al, 2021 ; Shetty and Fitzsimmons, 2021 ). Therefore, the third hypothesis is proposed in this study:…”
Section: Theoretical Background and Hypothesis Formulationmentioning
confidence: 99%
“…It has found resonance in the world of sport (van Rijn et al , 2019) as it has the capacity to exact significant commercial leverage (Toscani and Prendergast, 2018), reach substantive audiences (Woisetschläger and Michaelis, 2012), enhance brand awareness and reputation (van Rijn et al , 2019) and promote fans’ identification (Lee et al , 2020). Moreover, sponsorship represents a sophisticated means of inciting consumption (Dos Santos et al , 2019 and benefits from fans’ affective relationships with their team (Velicia Martín et al , 2020). It is this relationship between sponsor and team that is the catalyst for the sponsor and the fan developing a long-term, strategically essential relationship (Thomas, 2014).…”
Section: Introductionmentioning
confidence: 99%